Una nueva especie de Arbutus (Ericaceae, Arbuteae) de la Sierra Madre Occidental, México - Gonzalez Elizondo, M. Socorro; Gonzalez Elizondo, Martha (Instituto de Ecología, A.C., 1992)
Arbutus madrensis, from the States of Sinaloa, Durango, Jalisco and Nayarit is described. The new spipcies is a common tree in pine and pine-oak forests of the Sierra Madre Occidental between 2400 and 2800 m. It can be distinguished from other madroños by its checkered and persistent bark present even on the last twigs, and the largo, widely ovate to elliptic leaves with ferruginous, non glandular pubescence.